Microbial enhancement of oil recovery : recent advances : proceedings of the 1992 International Conference on Microbial Enhanced [sic] Oil Recovery - Premuzic, E. T.; Woodhead, Avril D. (Developments in petroleum science, 1993)
This volume is concerned with many aspects of petroleum microbiology and biochemistry, all with strong commercial applications. Worldwide research on the major topic, MEOR (Microbially Enhanced Oil Recovery) is comprehensively covered under experimental work, field applications and modeling. The challenge of formulating a complete in situ MEOR system (microorganisms, nutrient package, and other amendments) is explored together with the future needs in the design and execution of this new biotechnology.